DAKWAH UKHUWAH DAN SIYASAH : MISI PENDIDIKAN UMAT DALAM PEMIKIRAN DAN PERGERAKAN MOHAMMAD NATSIR - AGUS SUSILO SAEFULLAH (CV. ALIM'SPUBLISHING, 2024)
This pupose is structured to describe Mohammad Natsir with his movements in educating people through their conceptions and practice directly in the world of da'wah and politics in the field. This research presents the struggle of Natsir in guiding the people with da'wah, then unifying all the potential of the people in the frame of ukhuwah, as well as efforts to keep da'wah with siyasah as a form of struggle for the creation of an ideal religious, national and state life. This research is carried out through a qualitative approach formed by the study of figures through relevant literature and presented in the form of historical chronological descriptions with a sequence starting from biographies, educational concepts, propaganda movements, efforts of people's unity, and practical political movements of Mohammad Natsir aimed at providing education to the people. Keywords: People Education, Dakwah, Siyasah, Ukhuwah